61 Survival of patients from the south-east region of Ireland following st-elevation myocardial infarction compared with the rest of Ireland. (6th October 2022) - Laffan, J; Foley, A; Blake, G; Maree, A; Crowley, J; McCreery, C; Kearney, P; Kiernan, T; Owens, P; Kennedy, M; Byrne, RA
Abstract : Background: Guidelines advise that patients suffering ST-elevation myocardial infarction (STEMI) are revascularized as quickly as possible. If a patient is likely to receive primary percutaneous coronary intervention (PPCI) within 120 mins from diagnosis then this is the preferred treatment strategy. PPCI can only be delivered in specialist centres and timely access can be determined by geographical location. In the south-east region of Ireland, currently only in-hours PPCI care is provided in a single specialist centre. We wished to determine whether patients from the South East had different survival following STEMI than those in the rest of Ireland. Methods: All STEMI patients from January 2013 until March 2018 were identified from the Irish national acute coronary syndrome (ACS) registry. Ethical approval and a consent declaration were obtained before accessing data. STEMI patients treated in the single regional specialist centre in the south-east region were identified from an internal hospital database. Patients treated in the south-east region comprised those treated at either the single regional specialist centre and those patients treated after transfer to specialist centres outside the region. The comparator group comprised the remainder of patients with STEMI in the rest of Ireland. Survival was determined from the national death register. Proximity to nearest primary PCI centre was determined from Google Maps. Statistical analyses were performed using Stata. Results: 7, 483 patients were included in the analysis – 678 in the south-east region (371 treated in the regional centre, 307 transferred outside the region), 6, 805 in the rest of Ireland. Minimum follow up was 3 years, median follow up 5.5 years. Baseline characteristics are displayed in table 1 . Patients in the South East had similar survival (83.6%) to those in the rest of Ireland (81.9%), Log-Rank p=0.11; HR 0.85 (p=0.088 95%CI 0.69–1.03) ( figure 1 ). Conclusion: Patients living in the south-east region of Ireland showed similar unadjusted survival following STEMI compared to patients living in the rest of Ireland.